How to Motivate Employees of Generation Y in China: From the Perspectives of Financial and Non-financial Rewards - Sun, Rui (2017)
Because of the retirement issues and shrinking generations, the influence of Generation Y employees in China is becoming increasingly significant. Consequently, it is essential to examine the effective motivational drivers of Generation Y employees in China in order to engage and support them more effectively in their companies and organizations. The first purpose of this study is to examine the factors that will decrease the motivation and satisfaction of Chinese employees of Generation Y towards jobs. Second purpose is to identify the effective rewards that can motivate Generation Y. The third purpose is to examine the factors that will influence the retention of Chinese employees of Generation Y.